2018
DOI: 10.1186/s12875-018-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prescribed medicines in older patients with multimorbidity and polypharmacy in general practice

Abstract: BackgroundTreatment complexity rises in line with the number of drugs, single doses, and administration methods, thereby threatening patient adherence. Patients with multimorbidity often need flexible, individualised treatment regimens, but alterations during the course of treatment may further increase complexity. The objective of our study was to explore medication changes in older patients with multimorbidity and polypharmacy in general practice.MethodsWe retrospectively analysed data from the cluster-rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 55 publications
4
25
0
Order By: Relevance
“…Nonadherence to medication leads to a lack of treatment effectiveness, increased hospital admissions, healthcare expenditures, and ultimately can lead to an overtreatment of a disease [22,23]. Due to the presence of multiple comorbidities that require multiple therapies, and, consequently polypharmacy, elderlies are more prone to compliance problems and nonadherence than younger [8,14]. In our study, a positive correlation between the adherence levels and age was found.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Nonadherence to medication leads to a lack of treatment effectiveness, increased hospital admissions, healthcare expenditures, and ultimately can lead to an overtreatment of a disease [22,23]. Due to the presence of multiple comorbidities that require multiple therapies, and, consequently polypharmacy, elderlies are more prone to compliance problems and nonadherence than younger [8,14]. In our study, a positive correlation between the adherence levels and age was found.…”
Section: Discussionsupporting
confidence: 53%
“…Medicines are the medical technology mostly used and, according to literature, the concomitant use of five or more medicines, the most widely accepted definition of polypharmacy, affects 40-50% of elderly in high-income countries [4][5][6][7]. The use of multiple medication contributes to an incorrect use of medicines by the elderly and may potentially increase the risk for a Drug Related Problems (DRPs) occurrence, therefore interfering with the treatment effectiveness and safety [8][9][10]. In this context, DRPs in the elderly account for a large percentage of emergency treatment and hospitalizations, increasing the costs with health in the most aged regions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that patients on the list changed their GP or have died. Since prescriptions frequently change,38 some patients with polypharmacy might not have qualified for the screening list when data was last exported. For all these reasons, the protocol allows GPs to skip patients on the screening list if they provide an explanation, or to recruit patients who are not on the list but fulfil the inclusion and do not meet the exclusion criteria.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Neuropsychological problems like delirium, acute renal failure and hypotension are the most common unwanted side effects [ 2 ].. Furthermore, polypharmacy can lead to problems with medication adherence, especially in older adults if associated with visual or cognitive decline as well as aging, resulting in unwanted outcomes such as treatment failure or hospitalizations [ 4 ]. The prevalence of polypharmacy at hospital admission in various countries was reported to be between 20 and 60% [ 5 7 ] and it was recently reported that rehospitalization results in a significant increase in the number of drugs given to patients at discharge.…”
Section: Introductionmentioning
confidence: 99%